Browallia speciosa Browallia, Amethyst Flower - Edward Gilman; Teresa Howe (EDIS, 2007)
This document provides an overview of Browallia, a plant known for its blue or white flowers. It highlights the plant’s preference for afternoon shade and its suitability for hanging pots. The document also details the optimal conditions for seed germination and the importance of not covering the seeds with soil. Additionally, it mentions the need to harden off the plants before outdoor planting and provides guidance on planting times for USDA hardiness zones 10 and 11. Original publication date October 1999.